Does Honesty Impact the Budgeting Process? A Bibliometric Analysis - Putra, Joni; Mirza. BR, Aryan Danil (FKIP Universitas Lampung, 2024)
Budgeting plays an important role in an organization, both in terms of planning, controlling and decision making. In addition, the budget is also to improve coordination and communication between superiors and subordinates. Because of the involvement of managers in the budgeting process, honesty becomes a very important trait for every manager to have so that the budget is presented factually. This research seeks to map the evolution of scholarly research around the impact of honesty on the budgeting process using the bibliometric analysis method. This research analyzed articles published between 1991 and 2024 in Scopus-indexed journals. Data was extracted from the Scopus database and citation counts were calculated using Publish or Perish. Microsoft Excel was used for data processing, and Vos Viewers visualized the results. The objectives were to identify trends, citation patterns, leading authors, and explore the future of honesty and budgeting in the field. This research can help practitioners and academics in mapping related topics in future research.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.123-133